Non-viral expression of chimeric antigen receptors with multiplex gene editing in primary T cells - Cappabianca, Dan; Li, Jingling; Zheng, Yueting; Tran, Cac; Kasparek, Kassandra; Mendez, Pedro; Thu, Ricky; Maures, Travis; Capitini, Christian M.; Deans, Robert; Saha, Krishanu (Frontiers in Bioengineering and Biotechnology, 2024)
Efficient engineering of T cells to express exogenous tumor-targeting receptors such as chimeric antigen receptors (CARs) or T cell receptors (TCRs) is a key requirement of effective adoptive cell therapy for cancer. Genome editing technologies, such as CRISPR/Cas9, can further alter the functional characteristics of therapeutic T cells through knockout of genes of interest while knocking-in synthetic receptors that can recognize cancer cells. Performing multiple rounds of gene transfer with precise genome editing, termed multiplexing, remains a key challenge, especially for non-viral delivery platforms. Here, we demonstrate the efficient production of primary human T cells incorporating the knockout of three clinically relevant genes (B2M, TRAC, PD1) along with non-viral transfection of a CAR targeting the disialoganglioside GD2.Multiplexed knockout results in high on-target deletion for all three genes, with low off-target editing and chromosome alterations. Incorporating non-viral delivery to knock-in a GD2-CAR resulted in a TRAC-B2M-PD1 deficient GD2 CAR T cell product with a central memory cell phenotype and high cytotoxicity against GD2-expressing neuroblastoma target cells. Multiplexed gene-editing with non-viral delivery by CRISPR/Cas9 is feasible and safe with high potential for the rapid and efficient manufacturing of highly potent allogeneic CAR T cell products.